(untitled) (New York, 2006)
This latest addition to the Lange Current Series features alphabetically-organized, easy-to-read, two-page bulleted spreads covering everything from syndromes and symptoms to diagnosis and treatment for all areas of cardiology. This information-packed quick reference is perfect for busy clinicians who don't have the time to consult with large references or online databases that are too comprehensive for their immediate treatment needs.
Keywords: Cardiovascular system,Cardiovascular Diseases,Cardiovascular Diseases,Hệ thống tim mạch.; Diseases., diagnosis., therapy